2021
DOI: 10.1007/s10916-021-01727-6
|View full text |Cite|
|
Sign up to set email alerts
|

Technology Acceptance of a Machine Learning Algorithm Predicting Delirium in a Clinical Setting: a Mixed-Methods Study

Abstract: Early identification of patients with life-threatening risks such as delirium is crucial in order to initiate preventive actions as quickly as possible. Despite intense research on machine learning for the prediction of clinical outcomes, the acceptance of the integration of such complex models in clinical routine remains unclear. The aim of this study was to evaluate user acceptance of an already implemented machine learning-based application predicting the risk of delirium for in-patients. We applied a mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…An important aspect is the acceptance by healthcare professionals and the actual use of such system in clinical routine. A previous evaluation of a similar tool, predicting delirium in hospitalized patients, showed a high user acceptance regarding ease of use and usefulness [ 23 ]. Naturally, we aim to include user satisfaction and acceptance of this technology when it comes to predicting dysphagia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important aspect is the acceptance by healthcare professionals and the actual use of such system in clinical routine. A previous evaluation of a similar tool, predicting delirium in hospitalized patients, showed a high user acceptance regarding ease of use and usefulness [ 23 ]. Naturally, we aim to include user satisfaction and acceptance of this technology when it comes to predicting dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…
Fig. 1 Visualization of the machine learning-based dysphagia prediction in the hospital information system ( a ) [ 23 ] and in a web application ( b ). This screenshot is fictional and not referring to a real patient
…”
Section: Methodsmentioning
confidence: 99%
“…If an AI model is not accepted by the users, it will not influence clinical decision-making 69. Factors such as usefulness and ease of use, which are described in the technology acceptance model, are demonstrated to improve the likelihood of successful implementation and should therefore be taken into account 70 71. Furthermore, implementation efforts should be accompanied by clear and standardised communication of AI model information towards end users to promote transparency and trust, for example, by providing an ‘AI model facts label’ 72.…”
Section: Phase Iv: Implementing and Governing Of Aimentioning
confidence: 99%
“…The type of clinician involved in implementing machine learning tools was most commonly a physician (n=3, 30.0%) or nurse (n=3, 30.0%). Regarding the PROGRESS-PLUS criteria (online supplemental appendix 9), seven studies reported patient or clinician sex [27][28][29][30][31][32][33] and four studies reported additional PROGRESS-PLUS criteria (race, type of health insurance, rural/urban). 27 28 34 35 The demographic variables were only calculated for studies that reported them.…”
Section: Patient Characteristicsmentioning
confidence: 99%